The History of Education in West Java, Indonesia: From Traditional Era toward Modern Era - Suwirta, Andi (EDUCARE, 2009)
ABSTRACT: The history of education in West Java, Indonesia has been so long. If it is begun with informal education in family life, then its history can be started since people have been familiar with family life, a period of time that has never ended its beginning (time of immemorial) and its ending. Meanwhile, non-formal education is acquired from social interaction between an individual and another, between an individual and his community, and between a community and its surrounding community. The true formal education was gained since Sundanese people in West Java interacted with the great tradition, from the religion and civilization of Hinduism-Buddhist, Islam and Western. These three waves of civilization had influenced our national life, from old times up to recent times, included education sector. This paper, however, tried to discuss the history of education in West Java, its growth and development which had been existed since its earliest time â as long as the existing sources were possible â until the latest education development. Therefore, this paper tried to study the history of education in West Java, starting from Hinduism-Buddhist, Islam, Dutch and Japanese colonial, national independence and up to this recent development period.KEY WORDS: history of education, West Java, Sundanese people and three waves of civilization in Indonesia.About the Author: Andi Suwirta, M.Hum. is a Lecturer at the Department of History Education of UPI (Indonesia University of Education) in Bandung and Chairperson of ASPENSI (Association of Indonesian Scholars of History Education). He can be reached at: andisuwirta@yahoo.comHow to cite this article? Suwirta, Andi. (2009). âThe History of Education in West Java, Indonesia: From Traditional Era toward Modern Eraâ in EDUCARE: International Journal for Educational Studies, Vol.1(2) February, pp.129-140. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 7, 2008); Revised (January 17, 2009); and Published (February 17, 2009).